IMPLEMENTASI MICRO DIGITAL LEADING MAHASISWA INSTITUT AGAMA ISLAM NEGERI LHOKSEUMAWE - Zulkhairi Zulkhairi; Edy Rosadi; Mesiono Mesiono (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Practical Implementation of Micro Digital Leading Educational management is a logical consequence of changing times. This qualitative research examines the implementation of micro digital leading students of the Islamic Education Management Study Program, Faculty of Tarbiyah, and Teacher Training at the Lhokseumawe State Islamic Institute. The data collection instrument used was a questionnaire in the form of a statement. The results showed that Micro Digital Leading is a pattern and model of education management with computerization and digital technology, so it is very helpful and makes it easier for every user of educational services anywhere and anytime. and Management of schools and madrasas with a leading digital approach including digital libraries, digital laboratories, digital learning, digital presence, Digital Report Application, school digital marketing, digital website, and school information, and others.